A study on the interactive relationship between the environmental NGOs and the media in Sweden - Zhang, Rui (2009)
In this paper the interactive relationship between environmental NGOs and the media in Sweden is investigated. The paper is based on an empirical study from the information which has been collected from seven interviews with the environmental communicators, journalists and a PR consultant about how these environmental NGOs and journalists communicate with each other. With the theories of symbolic interactionism and environmental communication, the author aims to profoundly describe and analyze how the environmental NGOs interact with the media in Sweden. After interview discussion and interpretation, this paper shows that the relationship between these environmental NGOs and the media is cooperative and strategic, therefore most of NGOs have their own communication strategies, whereas some of which being used are not acknowledged by the environmental communicators. The paper also illustrates that the goal for NGOs in their communication with the media is to get a large number of media coverage so as to gain social influence on policy making or to arouse public awareness, etc. Though the communication strategies are helpful, it is inevitable that the environmental communicators may meet some problems when communicating with the journalists because of different perspectives.